Exploring the Inflammatory Pathogenesis of Colorectal Cancer by Assessing the Levels of the Markers Aflatoxin-B1, CARD-9, and Dectin-1 - Saeed, Layla Mahmood; ALabassi, Hazima Mossa (Iraqi Journal of Science, 2026)
Colorectal cancer (CRC) is one of the leading causes of cancer-related morbidity and mortality worldwide, with a growing incidence in developing countries such as Iraq. Chronic inflammation and exposure to environmental toxins like aflatoxin-B1 may influence disease development and progression. This study investigates the role of aflatoxin-B1, caspase recruitment domain-containing protein 9 (CARD-9), and Dectin-1 in CRC among Iraqi male patients, including newly diagnosed cases and those under chemotherapy. A total of 88 participants (60 CRC patients aged 25-70 and 28 healthy controls) were enrolled. Peripheral blood samples were withdrawn from each participant from four hospitals in Baghdad between October 2023 and January 2024. The participants were divided into three groups: 30 newly diagnosed CRC patients, 30 under treatment with chemotherapy (Folfox, Xeloda, Oxaliplatin), and 28 healthy individuals served as a control group. Serum levels of aflatoxin-B1, CARD-9, and Dectin-1 were determined by using an ELISA assay. The results showed no significant differences in aflatoxin-B1 levels across groups (p=0.24). However, CARD-9 levels were significantly higher in patients (p = 0.001), and Dectin-1 also showed significant differences (p = 0.002). Comparing the two patient groups, CARD-9 levels differed significantly (p < 0.001), while aflatoxin-B1 and Dectin-1 did not (p = 0.1, 0.06). Based on disease grades, CARD-9 showed significant differences in newly diagnosed patients (p = 0.044), while Dectin-1 showed significant differences in treated patients (p < 0.001). These findings highlight the potential role of CARD-9 and Dectin-1 as biomarkers in CRC progression and treatment monitoring.